HUBUNGAN KELEKATAN AMAN (SECURE ATTACHMENT) ANAK PADA ORANGTUA DENGAN KECERDASAN MORAL ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 3 KOTA PEKANBARU - Nadila, Iis; N, Zulkifli; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research was motivated by the law level of moral intelligence in TK Negeri Pembina 3 Pekanbaru city, which is related to the child to parent secure attachment, where the child behaves poorly, the child does not want to sharing food with friends, and lack of encouragement from parents, and the presence of a child does not dare to admit his mistake was seen when the child hit his friend. The aims of this research is to know correlation between secure attachment with moral intelligence of children aged 5-6 years in TK Negeri Pembina 3 Pekanbaru city. This type of research is quantitative a correlation research approach. As for the population of this research aged 5-6 years at TK Negeri Pembina 3 Pekanbaru city that consist of 80 children, of this research sample as many as 44 children which taken by using Slovin formula.. The technique of collecting data used was a observation and questioner. The technique of analyzing data used Pearson Product Moment Correlation by using SPSS program for windows Ver. 22. The result of hypothesis showed that there was a significant positive correlation between secure attachment and moral intelligence of children aged 5-6 years in TK Negeri Pembina 3 Pekanbaru city. It could be seen from the result of correlation coefficient that rxy= 0,561 and significant level is 0,000 < 0,05. The level of correlation between secure attachment and moral intelligence of children aged 5-6 years in TK Negeri Pembina 3 Pekanbaru city is in the middle category with the rank of determinan coefficient in the amount 31,5%, it means that secure attachment affect moral intelligence as much as 31,5%.Key Words: Secure Attachment, Moral Inteliligence, Children